Identifying the reality of training at King Khalid University and its effects on improving performance through job satisfaction among employees - Alsadig, Mohamed Ahmed; Omran, Abdallah Mushabab (Journal of Economic, Administrative and Legal Sciences, 2024)
This study aimed at identifying the reality of training at King Khalid University and its effects on improving performance through job satisfaction among employees. The study followed the analytical descriptive approach- the tool was a questionnaire distributed to an intentional sample of (132) male and female employees. The results of the study showed that the employees performance axis had the highest overall average of (4.08), then the employees job satisfaction with an average of (4.03), and finally the training' with an average of (3.91 out of 5), all with a grade of (great), and a positive relationship between training and job satisfaction was found, as well positive relationship between job satisfaction and level of performance. Based on the results, the researcher recommended paying attention to performance evaluation and linking it to the level of job satisfaction and training and creating an excellent work environment that helps employees to interact socially and builds trust and friendly relations among them. A proposal for complementary studies on the subject is also offered.
Keywords: reality of training; performance improvement; job satisfaction; employees at King Khalid University